DESIGN AND ANALYSIS OF VENTURI TURBINE TO RECOVER WASTE AIR ENERGY IN INDUSTRIAL APPLICATIONS. - Uthale, Suhas; Patil, Gajendra; Sabale, Mahadeo; Dhamal, Nitin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study focused onexperimentation and simulations in the development of waste air recovery system in industrial applications. The energy recovered from exhaust and ventilation systems of the industrial and commercial applications by the efficient and effective design. Recovery of energy wasted and released in terms of air discharge to the atmosphere after primary application is experimented, tested, and proven in this report at most optimal way. Conventional power generation from wind turbine takes up large swept area and it requires higher wind speeds to deliver rated power output. Our objective was to use compact design, consistent output from the energy freely released in the atmosphere after primary use in industries and commercial sector.Waste air recovery from industrial applications and design of turbine discussed in this paper is done in such a way that exhaust air coming out of duct at the discharge is directed through a funnel arrangement maintaining all the pressure criteria. Further the turbine is installed where the velocity of air is increased with venturi effect and directed towards the low-level turbine with the help of a nozzle, it has produced power, even at a lower air velocity or wind speed from the exhaust and ventilation system at a consistent load.Computational analysis is carried out on the theoretical results achieved in earlier stage, wherein measurements recorded are used to compute the right sizing and tap higher potential area keeping in mind the various factors required to install and run wind turbine generator.